Note of an Incised Cross Stone near the Burying Ground, Isle Martin, one of the Summer Isles, West Ross-shire (Proceedings of the Society of Antiquaries of Scotland, 1913)
The burying-ground is quite near the shore of a little bay, at the south-east corner of the island. The ancient stone, standing about four feet in height, with the cross carved on it, adjoins the burying-ground. The local tradition is that a priest lived a part of his life on Isle Martin, and died there, and his grave is marked by the stone in question.